Kombinasi One-step Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) dan Nucleic Acid Lateral Flow (NALF) sebagai Metode Deteksi Gen env-tm Virus Jembrana Strain Tabanan 1987 - Asmarani Kusumawati; Fatimah Fatimah (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Jembrana disease is an acute viral disease in Bali cattle that have short incubation period, high mortality and morbidity rate. Early diagnostic methods are needed to prevent the further spreading of this disease. In this study, we combined One-step RT-PCR and NALF methods to detect env-tm gene of Jembrana virus Tabanan 1987 strain. Viral RNA isolated from a spleen of the infected cattle was used as the template. One-step RT-PCR procedure was performed using oligoprobes labeled digoxigenin and right primer sequence that were designed using the primer3plus program based on the conserves region of env-tm gene from NCBI database. The product of one-step RT-PCR was tested using NALF method instead of electrophoresis. Positive result was shown by the appearance of dark lines on the test line of digoxigenin in NALF dipstick device.